1991
DOI: 10.1016/0006-8993(91)90473-9
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral amygdaloid multi-unit neuronal correlates of discriminative avoidance learning in rabbits

Abstract: Basolateral (BL) amygdaloid multi-unit activity was recorded as male albino rabbits learned to avoid a foot-shock unconditioned stimulus (US) by stepping in an activity wheel to an acoustic (pure tone) warning stimulus (CS+). A second tone (CS-) of different auditory frequency than the CS+ was presented in an irregular order on half of the conditioning trials but was never followed by the US. BL amygdaloid neurons developed, in the first session of conditioning, enhanced CS-elicited discharges relative to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 26 publications
2
84
3
Order By: Relevance
“…Four rabbits given sham (saline) injections and recording electrodes served as controls for assessment of the behavioral effects of the ibotenic acid lesions. Control data for assessment of the effects of the lesions on amygdalar training-related neuronal activity were obtained from rabbits in a previous study (Maren et al, 1991). Although there was a substantial time gap between the collection of these control data and the present study, the amygdalar changes observed in 1991 were replicated very recently with the same procedures (Freeman et al, 1997).…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations
“…Four rabbits given sham (saline) injections and recording electrodes served as controls for assessment of the behavioral effects of the ibotenic acid lesions. Control data for assessment of the effects of the lesions on amygdalar training-related neuronal activity were obtained from rabbits in a previous study (Maren et al, 1991). Although there was a substantial time gap between the collection of these control data and the present study, the amygdalar changes observed in 1991 were replicated very recently with the same procedures (Freeman et al, 1997).…”
Section: Methodsmentioning
confidence: 75%
“…Amygdalar and MG neurons are involved in aversively motivated instrumental conditioning processes, as well as in classical aversive conditioning. TIA develops rapidly in these areas during discriminative avoidance learning in rabbits (Gabriel et al, 1975(Gabriel et al, , 1976(Gabriel et al, , 1991bMaren et al, 1991) and amygdalar lesions severely impair behavioral acquisition (Poremba and Gabriel, 1997).…”
Section: Abstract: Limbic Thalamus; Cingulate Cortex; Amygdala; Learmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis was based on the following results: (1) the traininginduced plasticity of amygdalar, anterior cingulate cortical and MD thalamic neurons develops in parallel, in the early stages of learning; the plasticity in these areas diminishes as asymptotic levels of performance are attained (Applegate et al, 1982;Pascoe and Kapp, 1985;Nishijo et al, 1988;Gabriel, 1990;Maren et al, 1991); (2) amygdalar neurons send axons directly to the anterior cingulate cortex and the MD nucleus (Krettek and Price, 1978;Porrino et al, 1981;Price and Amaral, 1981;Price et al, 1987); and (3) the amygdala is involved in mediating acquisition of other aversively motivated behaviors (Blanchard and Blanchard, 1972;Spevack et al, 1975;Gentile et al, 1986;Hitchcock and Davis, 1987;LeDoux et al, 1988;Cahill and McGaugh, 1990;Willner et al, 1991;Helmstetter, 1992;Kapp et al, 1992;Fanselow et al, 1994).…”
Section: Abstract: Limbic Thalamus; Cingulate Cortex; Amygdala; Learmentioning
confidence: 99%